PKM PENGELOLAAN ARSIP NAGARI DALAM UPAYA MENDUKUNG PROGRAM SUSTAINABLE DEVELOPMENT GOALS - Marlini, Marlini; Emidar, Emidar; Zulfikarni, Zulfikarni; Rahmah, Elva; Erlianti, Gustina; Doni, Sefri (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
The objective of the Community Partnership Programme activities is to bolster the function of archives in the administration of village government in order to enhance services for the village community. This activity will solve problems holistically, beginning with the creation of official documents, the management of correspondence, the arrangement and use of archives, the depreciation of archives, and the maintenance of archives. The method offered to solve the problem is to conduct out comprehensive training (theory and practise) so that the ability of archive managers in Nagari Luak Kapau Alam Pauh Duo, Kec. Pauh Duo, Kab. South Solok can be improved in archival management. It is hoped that the results of the training and mentoring activities will create a systematic, organised village office archive so that the village government and the general public can easily and swiftly access the archives. The post-test results indicated that participants’ knowledge of managing village archives increased by 26% as a consequence of the training. This is demonstrated by the participants’ average pre-test score of 54/100, which increased to 82/100 after the post-test.